Do Stock Prices Impact Consumption and Interest Rate in South Africa? Evidence from a Time-varying Vector Autoregressive Model. (August 2015) - Aye, Goodness C.; Gupta, Rangan; Modise, Mampho P.
This article investigates the existence of spillovers from stock prices onto consumption and the interest rate for South Africa using a time-varying parameter vector autoregressive (TVP-VAR) model with stochastic volatility. In this regard, we estimate a three-variable TVP-VAR model comprising real consumption growth rate, the nominal three-months Treasury bill rate and the growth rate of real stock prices. We find that the impact of a real stock price shocks on consumption is in general positive, with large and significant effects observed at the one-quarter-ahead horizon. However, there is also evidence of significant negative spillovers from the stock market to consumption during the financial crisis, at both short and long horizons. The monetary policy response to stock price shocks has been persistent, and strong especially post the financial liberalisation in 1985, but became weaker during the financial crisis. Overall, we provide evidence of significant time-varying spillovers on consumption and interest rate from the stock market. JEL Classification: C11, C15, C32, E31, E32, E44, E52